An agile approach for managing requirements change to improve learning and adaptability - Shim, Woogon; Lee, Seok Won (Journal of Industrial Information Integration, 2019)
Nowadays agile development has become a mainstream development methodology. Yet agile is still lacking in how in-depth it deals with Requirement Engineering (RE) compared to the other development stages. There have been attempts to apply agile RE techniques to traditional development and conversely to apply traditional RE techniques to agile development. But the biggest problem is that it is difficult to maintain the essence of agile which is to “collaborate”, “(iterative and frequent) inspect and adapt”, and “deliver customer value”. In this paper, we define six criteria for an agile requirement management approach and propose a lightweight agile approach that maintains the characteristics of agile while combining the RE techniques of academia, business analyst, and agile & lean community. Furthermore, we show an industrial case study which we've applied our approach.
Keywords: Agile development; Agile requirements; Business analysts; Development methodology; Development stages; Industrial case study; Managing requirements; Requirement engineering